1961
DOI: 10.1152/ajplegacy.1961.200.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Use of coenzymes I and II in interconversion of testosterone and androstenedione

Abstract: Adult male guinea pig liver and kidney homogenates were able to utilize triphosphopyridine nucleotide as well as diphosphopyridine nucleotide in the conversion of testosterone and androstenedione and the reduced coenzymes in the reverse reaction. The oxidative process was much more effective than the reductive. The only other metabolite recognized was androsterone found in trace amounts during the reductive reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1962
1962
1978
1978

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In agreement with other studies (15,16), the canine renal tissue very actively metabolizes testosterone and androstenedione. In one human subject, Rivarola et al (9) did not find any extraction and interconversion of T and A by the kidney.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other studies (15,16), the canine renal tissue very actively metabolizes testosterone and androstenedione. In one human subject, Rivarola et al (9) did not find any extraction and interconversion of T and A by the kidney.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, several tissues (as studied in vitro) can interconvert and, in some cases, metabolize testosterone and androstenedione, as shown for the muscle (11), the skin (12,13), the prostate (14), the kidney (15,16), and the digestive tract (17).…”
Section: Introductionmentioning
confidence: 99%
“…This situation could arise as follows: It has been shown that T can be synthesized peripherally from both androstenedione (A) and dehydroepiandrosterone (D) (2)(3)(4)(5). Presumably this transformation occurs in the liver, and indeed this has been demonstrated by perfusion studies with dog liver (6).…”
mentioning
confidence: 99%